Genomic and pathological heterogeneity in clinically diagnosed small cell lung cancer in never/light smokers identifies therapeutically targetable alterations. Issue 1 (25th November 2020) - Ogino, Atsuko; Choi, Jihyun; Lin, Mika; Wilkens, Margaret K.; Calles, Antonio; Xu, Man; Adeni, Anika E.; Chambers, Emily S.; Capelletti, Marzia; Butaney, Mohit; Gray, Nathanael S.; Gokhale, Prafulla C.; et al.
Abstract : Small‐cell lung cancer (SCLC) occurs infrequently in never/former light smokers. We sought to study this rare clinical subset through next‐generation sequencing (NGS) and by characterizing a representative patient‐derived model. We performed targeted NGS, as well as comprehensive pathological evaluation, in 11 never/former light smokers with clinically diagnosed SCLC. We established a patient‐derived model from one such patient (DFCI168) harboring an NRAS Q61K mutation and characterized the sensitivity of this model to MEK and TORC1/2 inhibitors. Despite the clinical diagnosis of SCLC, the majority (8/11) of cases were either of nonpulmonary origin or of mixed histology and included atypical carcinoid ( n  = 1), mixed non‐small‐cell lung carcinoma and SCLC ( n  = 4), unspecified poorly differentiated carcinoma ( n  = 1), or small‐cell carcinoma from different origins ( n  = 2). RB1 and TP53 mutations were found in four and five cases, respectively. Predicted driver mutations were detected in EGFR ( n  = 2), NRAS ( n  = 1), KRAS ( n  = 1), BRCA1 ( n  = 1), and ATM ( n  = 1), and one case harbored a TMPRSS2‐ERG fusion. DFCI168 ( NRAS Q61K ) exhibited marked sensitivity to MEK inhibitors in vitro and in vivo. The combination of MEK and mTORC1/2 inhibitors synergized to prevent compensatory mTOR activation, resulting in prolonged growth inhibition in this model and in three other NRAS mutant lung cancer cell lines. SCLC in never/former light smokers is rare and is potentially a distinct disease entity comprised of oncogenic driver mutation‐harboring carcinomas morphologically and/or clinically mimicking SCLC. Comprehensive pathologic review integrated with genomic profiling is critical in refining the diagnosis and in identifying potential therapeutic options. Abstract : Small‐cell lung cancer occurs infrequently in never/former light smokers. We performed targeted NGS, as well as comprehensive pathological evaluation, in 11 never/former light smokers with clinically diagnosed SCLC. The majority of cases were either of nonpulmonary origin or of mixed histology. Predicted driver mutations were detected in EGFR, NRAS, KRAS, BRCA1, and ATM, and one case harbored a TMPRSS2‐ERG fusion.